The Effect of Continuous Grazing on Herbaceous Species Composition, Basal Cover and Production on Three Soil Types in the North West Province, South Africa - Jordaan, Franci; Rooyen, Jaco v (International Journal of Sustainable Agricultural Research, 2021)
Rangeland health is normally measured by soil condition, grass species composition as well as its acceptability to grazing herbivores. The impact of grazing on community structure and ecosystem functioning is a key issue for rangeland management in order to maximize livestock production and sustainability of the operations. Year-round continuous grazing is the management strategy used in the communal areas of the North West Province of South Africa. In this study the effect continuous grazing on herbaceous species composition, basal cover and production on different soil types was tested. It was clear from the results that the effect of continuous grazing was the biggest on the andesitic soils (high clay), then the diabase soils (medium clay), whilst the effect on the quartzite soils was limited to even positive. The end result was that the different soil types in a continuous grazing system led to serious selective grazing in this study.